Characteristics and Factors Associated with Pain in Older Homeless Individuals: Results from the HOPE HOME Study - Landefeld, John C. (J Pain, 2017)
Individuals experiencing homelessness in the United States are aging; little is known about chronic pain in this population. In a cross-sectional, population-based study, we interviewed 350 homeless individuals aged 50 and older to describe pain experienced by older persons experiencing homelessness and to assess factors associated with chronic moderate to severe pain, defined as pain lasting ≥3 months, with a past week average severity score of 5–10 (scale 0–10). The median age of participants was 58 years. Participants were predominantly African American (79.6%) and male (77.3%). Overall, 46.8% reported chronic moderate to severe pain. Almost half of participants reported a diagnosis of arthritis (44.3%) and one-third reported symptoms consistent with post-traumatic stress disorder (PTSD, 32.8%). Three-quarters (75.3%) endorsed a personal history of abuse. In multivariate analyses, PTSD (AOR: 2.2, CI 1.4–3.7), arthritis (AOR: 4.8, CI 3.0–7.8), and history of experiencing abuse (AOR: 2.4, CI 1.3–4.3) were associated with chronic moderate to severe pain. HIV status, diabetes, depressive symptoms, and substance use were not associated with pain. Clinicians should consider the management of associated mental health conditions and the sequelae of experiencing abuse in the treatment of chronic pain in older adults experiencing homelessness.